2006
DOI: 10.1159/000097367
|View full text |Cite
|
Sign up to set email alerts
|

Association of Angiotensin I-Converting Enzyme Gene Insertion/Deletion Polymorphism and IgA Nephropathy: A Meta-Analysis

et al.

Abstract: Background/Aims: The angiotensin I-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism has been extensively examined for the association with immunoglobulin A (IgA) nephropathy (IgAN), however, conflicting results have occurred. We performed a meta-analysis to evaluate the association of ACE I/D polymorphism with IgAN in different ethnic groups. Methods: 11 studies testing the association between ACE I/D polymorphism and IgAN susceptibility, and 9 studies testing the association of ACE I/D with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 75 publications
1
33
2
1
Order By: Relevance
“…Indeed, comparative analyses between 1339 patients with IgA and 1881 healthy controls found that the DD compared with the II and ID genotype was associated with a more than double incidence of IgA nephropathy in Asians, but with a similar risk of disease in whites. On the contrary, comparative analyses between 2706 progressors and 1578 nonprogressors found that the ACE I/D polymorphism remarkably affected the risk of ESKD in both populations, to the extent that Asian and white carriers of the DD genotype had, respectively, a 78% and 90% excess incidence of ESKD compared with carriers of the II or ID genotypes considered together (21).…”
Section: Nondiabetic Renal Diseasementioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, comparative analyses between 1339 patients with IgA and 1881 healthy controls found that the DD compared with the II and ID genotype was associated with a more than double incidence of IgA nephropathy in Asians, but with a similar risk of disease in whites. On the contrary, comparative analyses between 2706 progressors and 1578 nonprogressors found that the ACE I/D polymorphism remarkably affected the risk of ESKD in both populations, to the extent that Asian and white carriers of the DD genotype had, respectively, a 78% and 90% excess incidence of ESKD compared with carriers of the II or ID genotypes considered together (21).…”
Section: Nondiabetic Renal Diseasementioning
confidence: 92%
“…Most studies evaluated the relationships between ACE I/D and adult polycystic kidney disease (APKD) or IgA nephropathy. These studies were recently reviewed in two comprehensive meta-analyses showing that this polymorphism is not associated with the progression of APKD (20) but may affect both the incidence and progression of IgA nephropathy, although to a different extent in different considered populations (21). Indeed, comparative analyses between 1339 patients with IgA and 1881 healthy controls found that the DD compared with the II and ID genotype was associated with a more than double incidence of IgA nephropathy in Asians, but with a similar risk of disease in whites.…”
Section: Nondiabetic Renal Diseasementioning
confidence: 99%
“…Huang et al 19 conducted a meta-analysis, and provided evidence for genetic variation at the putative promoter region of Fc fragment of IgA conferring susceptibility to IgAN, suggesting -27C and its haplotype might be causative for the susceptibility among the Chinese Han population. Yong et al 20 performed a meta-analysis to evaluate the association of ACE I/D polymorphism with IgAN in different ethnic groups, and reported that ACE I/D polymorphism was associated with IgAN. Those results indicated that the gene polymorphism of some gene sites was associated with IgAN risk.…”
Section: Discussionmentioning
confidence: 99%
“…There have been various studies (Yong et al 2006;Nonoguchi et al 2007) reporting on varying renal outcome in patients with IgAN in respect of their ACE gene profile. The D alelle is believed to affect the renoprotective effects of ACEI/ARB therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been recent reports (Yong et al 2006;Nonoguchi et al 2007) that ACE ID polymorphism influences the responses of patients with IgAN to ACEI/ARB therapy. In a recent report, Dillon (2004) suggested that polymorphism of the ACE gene may have so far failed to predict either susceptibility to or progression of IgA nephropathy, but the D allele could predict a favourable response to renin-angiotensin blockade.…”
Section: Introductionmentioning
confidence: 98%